Understanding the Factors Influencing Consumer Trust and Satisfaction in Meituan’s Information Technology Services: A Quantitative Study in Anhui, China - WEN, HAIGANG; Chen, Yue (Pacific International Journal, 2024)
This study investigates the factors influencing consumer trust and satisfaction in Meituan’s information technology services in Anhui, China. Through a quantitative approach involving a cross-sectional survey of 200 respondents from Hefei City, this research examines the impact of service quality, user experience, perceived value, and brand reputation on consumer trust and satisfaction. The findings reveal significant positive relationships between these variables, highlighting that improvements in these areas can enhance consumer trust and satisfaction. The study contributes to the existing literature by providing a region-specific analysis and offers actionable insights for Meituan and similar service providers to tailor their strategies for better customer retention and loyalty.